Passage to Nowhere - Sehgal, Ikram (Dhaka PROBE Printers ltd., 2009)
On Pakistan's foreign policy during the period December 1987 to June 2003.
Include Index and Colour Illustration
Keywords: Pakistan -- Diplomatic relations -- Politics and government